Leasehold: An institutional framework for understanding nonprofit governance in a civil society context - Martin M. Greller (Administrative Sciences, 2015)
Nonprofit organizations play a role in the creation of a society that is civil, and it is an important one that neither the state nor for-profit organizations undertake. This raises the question of governance and accountability, which is often addressed by looking to agency-based models from the private sector. The acknowledged problem is that the agency's notion of owners does not translate well to nonprofits. Adapting the concept of leasehold (wherein the managers and organization operate with broad autonomy, using resources supplied by supporters in exchange for the promise that specific societal value will be created, and are accountable for doing so) allows for a more flexible and responsive arrangement. It also suggests a mechanism whereby many independent nonprofits taking multiple approaches help civil society evolve.
Keywords: 350; nonprofit; governance; agency theory; leasehold model; civil society